Thermodynamic analysis, synthesis, characterization, and evaluation of 1-ethyl-3-methylimidazolium chloride: Study of its effect on pretreated rice husk (2024)
This work is focused on the determination of the optimal reaction conditions to synthesize the ionic liquid 1-ethyl-3-methylimidazolium chloride ([EMIM][Cl]) and assess its suitability for the pretreatment of rice husk. The modified UNIFAC (UNIversal quasi-chemical Functional-group Activity Coefficients) approach for ionic liquids is used to develop a thermodynamic model that describes the reactive system methylimidazole (MIM), chloroethane (C2H5Cl) and [EMIM][Cl]. The model allows to study the phase equilibria coexistence (vapor–liquid equilibria and solid–liquid equilibria) and yields the theoretically optimal conditions to synthesize the ionic liquid. The model predictions are validated with the available experimental and reported data. By implementing the developed model, a simple way to synthesize ionic liquid [EMIM][Cl] was found allowing to study its influence on the structure and morphology of pretreated rice husk. The lignocellulosic materials involved in this study are characterized by their composition, enzymatic digestibility, scanning electron microscopy, and crystallinity. Compared to untreated material, [EMIM][Cl]-pretreated rice husk produces cellulose that can be efficiently enzymatic hydrolyzed with high sugar yields. This work offers a suitable methodology to include the synthesis and thermodynamics of the solvent media within the design of low-cost ionic liquids for lignocellulosic biomass pretreatment.